Corrosion potential measurement of coated steel in salt spray environment - 383872 Ravinderpal Kaur Jaj (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Mechanical Engineering (Material)) - Universiti Teknologi Malaysia, 2004